If A = \begin{bmatrix} -3 &6 \\-2 &4 \end{bmatrix}  then show that A^3=A

 

 

 

 
 
 
 
 

Answers (1)

A = \begin{bmatrix} -3 &6 \\-2 &4 \end{bmatrix}

A ^2= \begin{bmatrix} -3 &6 \\-2 &4 \end{bmatrix}\begin{bmatrix} -3 &6 \\-2 &4 \end{bmatrix}

\Rightarrow \begin{bmatrix} 9-12 &24-18 \\6-8 &-12+16 \end {bmatrix}\Rightarrow \begin{bmatrix} -3 &6 \\-2 &4 \end{bmatrix}

A ^3= \begin{bmatrix} -3 &6 \\-2 &4 \end{bmatrix}\begin{bmatrix} -3 &6 \\-2 &4 \end{bmatrix}= \begin{bmatrix} -3 &6 \\-2 &4 \end{bmatrix}

LHS=RHS=A

Hence Proved.

 

Preparation Products

JEE Main Rank Booster 2021

This course will help student to be better prepared and study in the right direction for JEE Main..

₹ 13999/- ₹ 9999/-
Buy Now
Rank Booster NEET 2021

This course will help student to be better prepared and study in the right direction for NEET..

₹ 13999/- ₹ 9999/-
Buy Now
Knockout JEE Main April 2021 (Subscription)

An exhaustive E-learning program for the complete preparation of JEE Main..

₹ 6999/- ₹ 5/-
Buy Now
Knockout NEET May 2021

An exhaustive E-learning program for the complete preparation of NEET..

₹ 22999/- ₹ 14999/-
Buy Now
Knockout BITSAT 2020

It is an exhaustive preparation module made exclusively for cracking BITSAT..

₹ 4999/- ₹ 1999/-
Buy Now
Exams
Articles
Questions